Phenothiazine and pyridine-N-oxide-based AIE-active triazoles: synthesis, morphology and photophysical properties. Issue 12 (11th February 2015) - Belei, Dalila; Dumea, Carmen; Bicu, Elena; Marin, Luminita
<x xml:space="preserve">Abstract</x> AIE triazoles based on phenothiazine and pyridine-N-oxide units provided micro- and nano-crystals with an emission enhancement of 233-fold higher.